Comparison of Cu-CHA-zeolites in the hybrid NSR-SCR catalytic system for NOx abatement in mobile sources - Molina-Ramírez, Sergio; Cortés-Reyes, Marina; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Alemany-Arrebola, Luis José (MDPI, 2023)
DeNOx activity in a NSR–SCR hybrid system of two copper-containing chabazite-type zeolitic catalysts was addressed. A Pt-Ba-K/Al2O3 model catalyst was used as the NSR (NOx storage and reduction) catalyst. For the SCR (selective catalytic reduction) system, two Cu-CHA zeolites were synthesized employing a single hydrothermal synthesis method assisted with ultrasound and incorporating Cu in a 2 wt.%, 2Cu-SAPO-34 and 2Cu-SSZ-13. The prepared catalysts were characterized, and the crystallinity, surface area, pore size, HR-TEM and EDX mapping, coordination of Cu ions and acidity were compared. The NH3 storage capacity of the SCR catalysts was 1890 and 837 μmol NH3·g−1cat for 2Cu-SAPO-34 and 2Cu-SSZ-13, respectively. DeNOx activity was evaluated for the single NSR system and the double-bed NSR–SCR by employing alternating lean (3%O2) and rich (1%H2) cycles, maintaining a concentration of 600 ppm NO, 1.5% H2O and 0.3% CO2 between 200 and 350 °C. The addition of the SCR system downstream of the NSR catalyst significantly improved NOx conversion mainly at low temperature, maintaining the selectivity to N2 above 80% and reaching values above 90% at 250 °C when the 2Cu-SSZ-13 catalyst was located. The total reduction in the production of NH3 and ~2% of N2O was observed when comparing the NSR–SCR configuration with the single NSR catalyst.
Keywords: Catalizadores; Motores diesel; Aire -- Contaminación -- Control; Control de la contaminación del aire; DeNOx hybrid technology; NSR–SCR; Cu-CHA zeolites; SAPO-34; SSZ-13